Post-thaw variability in litter decomposition best explained by microtopography at an ice-rich permafrost peatland. Issue 1 (1st January 2018) - Malhotra, Avni; Moore, Tim R.; Limpens, Juul; Roulet, Nigel T.
ABSTRACT: Litter decomposition, a key process by which recently fixed carbon is lost from ecosystems, is a function of environmental conditions and plant community characteristics. In ice-rich peatlands, permafrost thaw introduces high variability in both abiotic and biotic factors, both of which may affect litter decomposition rates in different ways. Can the existing conceptual frameworks of litter decomposition and its controls be applied across a structurally heterogeneous thaw gradient? We investigated the variability in litter decomposition and its predictors at the Stordalen subarctic peatland in northern Sweden. We measured in situ decomposition of representative litter and environments using litter bags throughout two years. We found highly variable litter decomposition rates with turnover times ranging from five months to four years. Surface elevation was a strong correlate of litter decomposition across the landscape, likely as it integrates multiple environmental and plant community changes brought about by thaw. There was faster decomposition but also more mass remaining after two years in thawed areas relative to permafrost areas, suggesting faster initial loss of carbon but more storage into the slow-decomposing carbon pool. Our results highlight mechanisms and predictors of carbon cycle changes in ice-rich peatlands following permafrost thaw.